DV-made Tibet: Domestic Videos, Elite Films, and the Work of Pema Tseden - Barnett, Robert (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
In the three decades after 1980, major changes took place in the ways in which culture in Tibet was produced, transmitted, and consumed.¹ These changes, however, were not evidence of the radical transformation often claimed as the result of digitization, but were brought about by earlier forms of technological development. In terms of music and radio, it was the arrival of cheap cassette players and recorders in Tibet in the late 1980s that allowed Tibetans to choose for the first time when to listen and, within the limits allowed by the market and the government, what to listen to (Dhondup
Keywords: 1-Cinéma; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

APPENDIX II: Tibetan Filmography/Videography - Barnett, Robert; Zhen, Zhang; Zito, Angela (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
Keywords: 1-Cinéma; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

APPENDIX I: Chinese and Non-Chinese Filmography/Videography - Cho, Ting-Wu; Zhen, Zhang; Zito, Angela (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
Keywords: 1-Cinéma; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

Chinese Independent Cinema in the Age of “Digital Distribution” - Gao, Dan (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
My chapter looks at Chinese independent cinema as an institutionalizing enterprise. In other words, although many filmmakers keep emphasizing the individualistic quality of their agenda or the idiosyncrasy of their film works, independent films have developed things in common, such as certain thematics, addresses, formalistic styles, and modes of production. Their survival is also predicated more and more on shared infrastructures of film communities, distribution agents, and exhibition networks. Of course, this does not mean that the institution of Chinese independent cinema is settled and finalized; it isn’t like a breed of crops circled by impermeable ideological or physical fences.
Keywords: 1-Cinéma; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

Filming Power and the Powerless: Zhao Liang’s Crime and Punishment (2007) and Petition (2009) - Li, Jie (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
This article discusses two recent works by emerging documentary auteur Zhao Liang, Crime and Punishment(2007) and Petition(2009). These penetrating observations of state-society relations in contemporary China render visible those who are un(der)represented, critique the deception of mass media images, and show the various complex ways in which power is connected to surveillance and visibility. Thus the filmmaker, his camera, and the spectators are implicated in power relationships as we cast voyeuristic, panoptic, activist, empathetic, or critical gazes upon the representatives of state power and upon the disenfranchised.
Keywords: 1-Cinéma; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Marking the Body: The Axiographics of the Visible Hidden Camera - Nornes, Abé Mark (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
This chapter contemplates the ethical dimensions of the specific brand of observational cinema found in China. Because there is no popular understanding of independent documentary—and also because filmmakers almost invariably use amateur video cameras and shoot alone—many subjects are oblivious to the fact that their images are being captured for films being screened around the world. It is in this sense that, while their cameras are perfectly visible, they are also hidden. This enables directors to capture “life unawares,” as if people were being shot by a hidden camera. In this context, directors make the films they want, ignoring the ethical implications of shooting people without being upfront about their intentions or asking for consent. The chapter closely examines a set of films to explore the axiographics of the documentary, in other words how ethics is rendered in the time and space of the moving image.
Keywords: 1-Cinéma; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Chinese Digital Shadows: Hybrid Forms, Bodily Archives, and Transnational Visions - Reynaud, Bérénice (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
Taking Hao Jie’s Single Man as a case study, this chapter discusses the effect of globalization on independent DV production—a home-grown phenomenon born out of the availability of DV cameras and computer editing software and the spreading of the internet. Starting as a marginalized practice without access to the domestic market, and expressing a desire to saturate the visual field with obfuscated images and to create a counter-archive (a counter-memory of the Chinese people), it attracted international attention, which in turn allowed it to have access to alternative forms of financing as well as the input of foreign talent. The fluidity of digital modes of production also contributed to an eradication of the boundaries between documentary and fiction. Instead, the real divide lies between “the desire for cinema” and “the desire for documentation.”
Keywords: 1-Cinéma; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

“To Whom Do Our Bodies Belong?”: Being Queer in Chinese DV Documentary - Robinson, Luke (DV-made China : digital subjects and social transformations after independent film, 2015)
In 1990s post-Reform China, a growing number of people armed with video cameras poured out upon the Chinese landscape to both observe and contribute to the social changes then underway. This digital turn has given us a 'DV China' that includes film and media communities across different social strata and disenfranchised groups. This study takes stock of these phenomena by surveying the social and cultural landscape of grassroots and alternative cinema practices.
Keywords: 1-Cinéma; 2-Étude de la réception; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

DV and the Animateur Cinema in China - Voci, Paola (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
Film scholarship on the movie-making, movie-viewing, and movie-circulating practices that have developed since the mid-1990s in China has appropriately emphasized the role played by the rise of digital video (DV) and its impact on independent and, in particular, documentary filmmaking. In this chapter, I want to explore one line of development in DV independent production that has received much less attention—what I call animateur cinema—which concerns short digital animations that are made by and/or circulated for online (or on-mobile) moviemakers/viewers. Fan-originated digital animation or egao animation can also be found online, but my focus is on animateur cinema
Keywords: 1-Cinéma; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Crossing Cameras in China: Christian Aesthetics and Realized Fictions - Zito, Angela (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
The films of director Gan Xiao’er are the first narrative features to take up Chinese Christians in their everyday concerns. This chapter discusses a pair of his films, one a fiction feature, the other a documentary made about taking that feature on the road and showing it in churches. It is about filmmaking practice—and especially documentary—as social occasion, as the concatenation between people of self-reflective moments of cultural creativity and critique. By social occasion, I mean that Gan has documented in the second film the moments of self-conscious “participation” in the fiction feature and in the documentary itself.
Keywords: 1-Cinéma; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Beyond Bollywood: the Cultural Politics of South Asian Diasporic Film. - Desai, Jigna (Taylor & Francis, 2004)
Beyond Bollywood is the first comprehensive look at the emergence, development, and significance of contemporary South Asian diasporic cinema. From a feminist and queer perspective, Jigna Desai explores the hybrid cinema of the 'Brown Atlantic' through a close look at films in English from and about South Asian diasporas in the United States, Canada, and Britain, including such popular films as My Beautiful Laundrette, Fire, Monsoon Wedding, and Bend it Like Beckham.
OCLC: 824549185
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé